Sistem Monitoring Berbasis IoT pada Pembangkit Listrik Tenaga Mikrohidro Tangsijaya - Tiara Verita Yastica; Muhammad Almaududi Pulungan; Meldi Rendra (Warta LPM, 2024)
The Micro Hydro Power Plant of Gunung Halu was established in 2007. While electricity from the national power grid is available in the village of Gunung Halu, not all hamlets receive a consistent power supply, particularly those with hilly topography and areas surrounded by forests like Dusun Tangsijaya. The existence of the micro hydro power plant in Tangsijaya is supported by a stable water flow from the river. However, one of the challenges faced by the operator is the lack of a monitoring system for the micro hydro power generator that can provide information about its condition, such as power output and electric current. Until now, the operator has checked the data by visiting the location of the micro hydro power plant directly, which is located outside the residential area. Manual recording relies on the existence of human resources and produces results with a low level of accuracy. In this community service activity, a monitoring system was installed at the Tangsijaya's micro hydro power plant. Leveraging Internet of Things (IoT) technology, this system can display data in real time, so that data visualization can be monitored by relevant parties. With a monitoring system, micro-hydro operators can control the usage and distribution of the generated electricity. In addition to obtaining records of daily electricity usage data, recorded data provide very valuable information in assessing current and potential electricity usage for making decisions related to electricity production. After the implementation of the monitoring system, the main benefits are felt by microhydro operators where the work processes they do become more efficient. Efficiency is obtained in terms of travel distance where operators do not need to visit the PLTMH location directly, and also efficiency in the recording process which no longer needs to be done manually.